Adhesion Of Candida Albicans To Digital Versus Conventional Acrylic Resins: A Systematic Review And Meta-analysis - Mohammed Nasser Alhajj; Esam Halboub; Norlela Yacob; Sadeq Ali Al‑Maweri; Siti Fauzza Ahmad; Asja Celebić; Hesham M. Al‑Mekhlafi; Nosizana Mohd Salleh (BioMed Central, Springer Nature., 2024)
Indexed by WOS/Scopus/ERA